Evaluation of bee pollen by characterizing its botanical origin, total phenolic content, and microbial load for the formulation of apitherapy products - Aysan Rezazadeh; Ahmad Reza Mehrabian; Hadi Maleki; Zahra Shakoori; Narges Zarei Golbaghi; Tayeb Sharifi; Hasan Yazdi; Mostafa Zarqami Amirsalari; Helia Hajihassani (PLoS ONE, 2025)
Bee pollen (BP) is a beehive product known for its therapeutic properties. In this study, we aimed to evaluate 38 BP samples harvested from January 2022 to September 2022 at apiaries located in 6 provinces of Iran. The botanical origin of BP samples was determined using Scanning Electron Microscopy (SEM). The total phenolic content (TPC) of BP samples was evaluated using the Folin_Ciocalteu method. The total aerobic mesophiles were observed using Plate Count Agar (PCA). Based on the predominant grains, most samples were classified as monofloral, identifying 23 plant families. The results indicated a direct relationship between the increased abundance of plant families Asteraceae, Brassicaceae, Rosaceae, and Caryophyllaceae and the increased amount of TPC in BP samples, with the most significant positive influence of the Brassicaceae plant family. The mean value of TPC of methanol extracts of BP samples was 18.48 ± 1.97 mg of gallic acid equivalents per g (GAE/g). The mean value of the total aerobic mesophiles was 23,668.12 colony-forming units per g (CFU/g). The results were based on hygiene standards for human consumption. The current study is considered the first step toward standardizing Iranian BP.